Diversity and Benefits of Asteraceae in Kapopo Ngatabaru Great Forest Park - Haruna Saprin S.; Rasyiid Mustafid; Iqbal Moh. (BIO Web of Conferences, 2024)
This study aims to determine the Asteraceae family's diversity, origin, and benefit in Kapopo Ngatabaru Great Forest Park, Central Sulawesi. The study was conducted in June 2023. The study used the exploration method. The results of this study found there are five species of Asteraceae in Kapopo Ngatabaru Great Forest Park: Chromolaena odorata, Porophyllum ruderale, Eleutheranthera ruderalis, Synedrella nodiflora, and Tridax procumbens. These five species are introduced species that have benefits as herbal medicine and pesticides.